2021
DOI: 10.14233/ajchem.2021.23037
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Characterization of Zinc Oxide Nanoparticles and their Incorporation into Glass Ionomer Cement for Inhibition of Streptococcus mutans

Abstract: In present study, zinc oxide nanoparticles were synthesised using Syzygium aromaticum and characterized using UV visible spectroscopy, SEM, XRD and FTIR techniques. The characteristic hexagonal structure of the ZnO nanoparticles was confirmed through XRD analysis. The UV-Visible spectrum showed a strong absorbance at 366 nm confirming the presence of ZnO and the peak at 496 cm-1 in FTIR indicated the Zn-O stretch bond. Average size of the zinc oxide nanoparticles obtained from SEM analysis was found to be 86 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Incorporation of NMs affected S. mutans viability and the expression of key genes for bacterial survival and growth. Anticariogenic properties were improved ZnO [ 65 ] Phytosynthesized using Syzygium aromaticum extract GC Fuji II GP ® (type II ii ) 50% NM in GIC, evaluation of antimicrobial potential (against Streptococcus mutans ) Incorporation of NMs provided antimicrobial activity to the GIC: IZ ~10.5 to 15.5 mm (depending on the S. mutans isolate) TiO 2 [ 66 ] Nanotubes, chemically synthesized, particle size 20 nm, diameter 10 nm Ketac Molar EasyMix™ (type II ii ) 3, 5, 7% NM in GIC, evaluation of CS, FS, μSBS, Ra, WL (after brushing simulation) Incorporation of NMs improved the mechanical properties and decreased weight loss after surface wear, without affecting adhesiveness to dentin. Best results at 5% NM: CS = 105.23 MPa, FS = 7.41 MPa, μSBS = 5.30 MPa, Ra = 0.3997/0.3851 μm (after/before brushing simulation), WL = 1.4%; control CS = 89.46 MPa, FS = 6.41 MPa, μSBS = 4.76 MPa, Ra = 0.4213/0.3127μm (after/before brushing simulation), WL = 3.8% MgO [ 67 ] Commercially available Ketac Molar EasyMix™ (type II ii ) 1, 2.5, 5, 10% NM in GIC, evaluation of ST, CS, DTS, μSBS Addition of NMs for up to 2.5% kept the setting time within the requirements of ISO standard, and increased cement strength, without affecting the adhesiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of NMs affected S. mutans viability and the expression of key genes for bacterial survival and growth. Anticariogenic properties were improved ZnO [ 65 ] Phytosynthesized using Syzygium aromaticum extract GC Fuji II GP ® (type II ii ) 50% NM in GIC, evaluation of antimicrobial potential (against Streptococcus mutans ) Incorporation of NMs provided antimicrobial activity to the GIC: IZ ~10.5 to 15.5 mm (depending on the S. mutans isolate) TiO 2 [ 66 ] Nanotubes, chemically synthesized, particle size 20 nm, diameter 10 nm Ketac Molar EasyMix™ (type II ii ) 3, 5, 7% NM in GIC, evaluation of CS, FS, μSBS, Ra, WL (after brushing simulation) Incorporation of NMs improved the mechanical properties and decreased weight loss after surface wear, without affecting adhesiveness to dentin. Best results at 5% NM: CS = 105.23 MPa, FS = 7.41 MPa, μSBS = 5.30 MPa, Ra = 0.3997/0.3851 μm (after/before brushing simulation), WL = 1.4%; control CS = 89.46 MPa, FS = 6.41 MPa, μSBS = 4.76 MPa, Ra = 0.4213/0.3127μm (after/before brushing simulation), WL = 3.8% MgO [ 67 ] Commercially available Ketac Molar EasyMix™ (type II ii ) 1, 2.5, 5, 10% NM in GIC, evaluation of ST, CS, DTS, μSBS Addition of NMs for up to 2.5% kept the setting time within the requirements of ISO standard, and increased cement strength, without affecting the adhesiveness.…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, recent studies have demonstrated that various INPs can be incorporated into conventional GICs to enhance their properties, and that there are comparatively few reports of pure silica particles in this application [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The findings of the present study have indicated that nano- and micro-silica can be uniformly distributed throughout the GIC matrix by simple manual spatulation.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, a range of inorganic nanoparticles (INPs) (i.e., Ag, AgVO 3 , Al 2 O 3 , BaSO 4 , Ca 5 (PO 4 ) 3 OH, Cu, CuO, MgO, Mg 2 SiO 4 , SiO 2 , TiO 2 , YbF 3 , ZnO ZrO 2 , bioactive glasses, amorphous calcium phosphate, graphene oxide, carbon nanotubes, and aluminosilicate nanoclays) has been incorporated into glass–ionomer cements with the objective of improving their mechanical, chemical, and/or biological properties [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In brief, enhanced antimicrobial properties are reported for Ag-, AgVO 3 -, Cu-, CuO-, MgO-, TiO 2 -, and ZnO-blended GICs [ 3 , 4 , 6 , 7 , 10 , 11 , 12 , 13 , 14 , 16 ]. The incorporation of silica (SiO 2 ), hydroxyapatites (Ca 5 (PO 4 ) 3 OH), and bioactive glasses is observed to give rise to superior cytocompatibility and bioactivity [ 18 , 20 , 21 , 22 , 23 ], and improved mechanical properties are noted for GICs blended with a wide range of metal and metal oxide nanostructures [ 3 , 4 , 5 , 6 ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation